Comparison of Filter Banks for High Quality Audio Coding - Brandenburg, Karlheinz; Eberlein, Ernst; Herre, Jürgen; Edler, Bernd (IEEE Int. Symp. on Circuits and Systems, 1992)
Perceptual coding techniques have recently been applied successfully to high-quality coding of digital audio signals. The basic perceptual coding system uses an analysis/synthesis system to map the time-domain data into a number of frequency-domain channels. A perceptual model is used to estimate the amount of noise shaping needed in order to avoid any audible noise due to the quantization of the frequency domain data. Different filterbanks have been applied to perceptual coding. A comparison of different filterbanks shows that there is no performance penalty for hybrid filterbanks compared to other solutions.<br